The Critical Success Factors (CSFS) model for Facilities Management (FM) of high-rise strata housing/ Farhan Md Dahlan - Md Dahlan, Farhan (2022)
High-rise strata (HRS) housing scheme is in high demand in major urban cities. Poor management practices by the management bodies in HRS housing scheme being a bone of contention among the residents and management body. Scarce mechanisms in the facilities management (FM) industry such as guidelines or standards of operation (SOP) as the reference point of the self-governance management have led to the lack of knowledge and strategies to improve their effectiveness in managing their strata housing. Additionally, HRS housing schemes aged more than ten (10) years post-construction show signs of obsolescence and incur great maintenance cost impact, albeit the topic which is under scarce research. Hence, this research fills this gap. This research aims to develop a Critical Success Factors (CSFs) Model towards the effectiveness of FM organisation managing HRS housing as the key management practices mechanism for management bodies. To achieve this aim, the research seeks to achieve three (3) research objectives which are: (i) to determine the critical success factors (CSFs) towards the effectiveness of FM organisations in managing Malaysian HRS housing. (ii) to analyse the relationship between the identified CSFs and the effectiveness of FM organisations in managing Malaysian HRS housing. (iii) to develop a CSFs model towards the effectiveness of FM organisations in managing Malaysian HRS housing.